Global research on health implications related to spirit possession: A scientometric review using the PubMed database - Perera, K.K.N.L. (The Library, University of Colombo, 2019)
Spirit Possession (SP) is generally termed as an abnormal human behavior triggered by spirits which are believed to inhabit the human body. The aim of this study was to map research productivity on SP based on the articles indexed in PubMed. The articles related to SP dated from 1990 to 2018 were retrieved from PubMed. A total of 88 articles were included for the analysis. They were published in 58 journals. ‘Culture, Medicine and Psychiatry’ was identified as the most productive (11 articles; 12.5%) journal, followed by ‘Transcultural Psychiatry’ (8 articles; 9%) and the ‘Journal of Religion and Health’ (4 articles; 4.45%). Uganda was the leading country with a highest number of published articles (9 articles; 10.22%), followed by the United Kingdom (7 articles; 7.95%), India (5 articles; 5.68%) and Ethiopia (5 articles; 5.68%). The highest number of articles were published in 2016. A large portion of articles (29 articles; 32.95%) were published by African countries. ‘Mental health’, ‘trauma’ and ‘culture’ were found to be the most frequently used MeSH terms. 10.22% of the publications (9 articles) have focused on involuntary mass SP in different populations, while 6.81% of the publications (6 articles) have focused on traditional healing methods related to SP. 7.95% of the articles (7 articles) have an association with the term ‘epilepsy’. There is a weak positive correlation (0.171) between the number of citations and the journal impact factor. 59.09% (52 articles) of papers are multi-authored, whereas 40.9% (36 articles) of papers are single authored. The degree of author collaboration is 0.59. The mean relative growth rate (R) of global SP articles is 0.16. The pattern of R values neither showed a positive nor a negative growth rate of SP articles published over the time period that was considered for this study.
Keywords: PubMed, research productivity, Scientometric, Spirit possession